Hubungan antara dukungan suami dan motivasi tenaga kesehatan tentang antenatal care dengan frekuensi kunjungan kehamilan - Hendrik Probo Sasongko; Febrika Nanda; Setyo Kurniawan; Sofwatul Mujayadah (Holistik Jurnal Kesehatan, 2026)
Background: Routine antenatal care (ANC) is crucial for the early detection of complications and the improvement of maternal and fetal health. However, the frequency of ANC visits in Indonesia has not yet reached optimal standards. Contributing factors include a lack of husband support and low motivation among health workers in providing education and support services. Purpose: To identify the relationship between husband support and health worker motivation regarding ANC and the frequency of ANC visits within the "Geliat Airlangga" program. Method: This study employed a quantitative approach with a cross-sectional design. A sample of 94 pregnant women participating in the Geliat Airlangga Program in the Sepanjang Community Health Center working area was selected using purposive sampling. Data collection was conducted using a questionnaire with established validity and reliability. Results: There was a significant relationship between husband support and the frequency of ANC visits (p = 0.000), and health worker motivation was also significantly associated with the frequency of ANC visits (p = 0.001). Multivariate analysis revealed that husband support was the most dominant factor influencing visit frequency (p = 0.000; OR = 6.087). Conclusion: Husband support and health worker motivation play vital roles in increasing the frequency of ANC visits. Efforts to enhance husband involvement and strengthen the role of health workers are essential within antenatal care programs.   Keywords: Antenatal Care (ANC) Visits; Health Worker Motivation; Husband Support.